Behavioral and Informational Drivers of Investment Decision Making: Insights into Investor Competencies and Decision Processes on the Pakistan Stock Exchange - Sattar, Rameez Abdul; Arif, Kashif; Shah, Syed Qasim; Riaz, Sana (Journal of Human Capital Development (JHCD), 2025)
This paper investigates the behavioral and informational determinants of individual investment decision making on the Pakistan Stock Exchange (PSX), with a particular emphasis on investor competencies and decision processes that reflect both cognitive and contextual influences. Recognizing that investment decisions are shaped not only by financial data but also by human perceptions, information processing capabilities, and personal goals, this study examines how firm image, accounting information, advocate guidance, and personal financial needs influence active investors’ choices. A structured questionnaire was administered to 384 active investors, and reliability was established through Cronbach’s alpha. Correlation and multiple regression analyses were employed to test the relationships among variables. Results indicate that all four factors significantly impact investment decisions, with personal financial needs emerging as the most influential predictor. These findings underscore the importance of integrating behavioral insights with conventional financial information to enrich understanding of investor decision making in an emerging market context. Moreover, the study contributes empirical evidence on how investors interpret and utilize different forms of information—a critical aspect of developing investor competencies, enhancing financial literacy, and reducing information asymmetry. The outcomes offer practical implications for policymakers, financial advisors, and educators seeking to cultivate more informed and resilient investor behavior, thereby advancing both individual decision capacity and broader financial market development. Ultimately, this research bridges financial decision making and human-centered perspectives, aligning with themes of workforce transformation, human and technology development, and inclusive growth emphasized within human capital development research